Batch-fabricated microinductors with electroplated magnetically anisotropic and laminated alloy cores - Park, JY; Han, SH; Allen, MG (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1999)
Although many integrated inductors have been made by integrated circuit and electronic packaging batch-fabrication techniques, their magnetic characteristics are inferior to their discrete counterparts, in part because of the relatively poor magnetic properties of integrated magnetic cores. If the permeability of an integrated magnetic core can be increased, the magnetic characteristics of microinductors based on these cores will improve. To address this issue, batch-fabricated, integrated magnetic devices incorporating electroplated magnetically anisotropic cores and electroplated copper coils are investigated. These devices are made by micromachining and electroplating techniques at low temperature, Three different geometries of inductors, each possessing two different core materials [permalloy (NiFe) and supermalloy (NiFeMo)] are presented, The cores have been rendered magnetically anisotropic by application of a magnetic field during electrodeposition, resulting in easy and hard axis orientations. In addition, some cores consist of a two-layer electrodeposit separated by a polyimide thin-film lamination, At low frequencies (less than several hundred kHz), the easy-axis devices have higher inductance than the hard-axis devices. However, the hard-axis devices have better performance at higher frequencies because of a far less steep falloff of material permeability as a function of frequency in the hard axis direction.